Active Versus Expectant Management for Preterm Premature Rupture of Membranes at 34-36 Weeks of Gestation and the Associated Adverse Perinatal Outcomes - Malú Flôres Ferraz; Thaísa De Souza Lima; Sarah Moura Cintra; Edward Araujo Júnior; Caetano Galvão Petrini; Mario Sergio Silva Gomes Caetano; Marina Carvalho Paschoini; Alberto Borges Peixoto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective: To compare the type of management (active versus expectant) for preterm premature rupture of membranes (PPROM) between 34 and 36 + 6 weeks of gestation and the associated adverse perinatal outcomes in 2 tertiary hospitals in the southeast of Brazil. Methods: In the present retrospective cohort study, data were obtained by reviewing the medical records of patients admitted to two tertiary centers with different protocols for PPROM management. The participants were divided into two groups based on PPROM management: group I (active) and group II (expectant). For statistical analysis, the Student t-test, the chi-squared test, and binary logistic regression were used. Results: Of the 118 participants included, 78 underwent active (group I) and 40 expectant management (group II). Compared with group II, group I had significantly lower mean amniotic fluid index (5.5 versus 11.3 cm, p = 0.002), polymerase chain reaction at admission (1.5 versus 5.2 mg/dl, p = 0.002), time of prophylactic antibiotics (5.4 versus 18.4 hours, p < 0.001), latency time (20.9 versus 33.6 hours, p = 0.001), and gestational age at delivery (36.5 versus 37.2 weeks, p = 0.025). There were no significant associations between the groups and the presence of adverse perinatal outcomes. Gestational age at diagnosis was the only significant predictor of adverse composite outcome (x2 [1] = 3.1, p = 0.0001, R2 Nagelkerke = 0.138). Conclusion: There was no association between active versus expectant management in pregnant women with PPROM between 34 and 36 + 6 weeks of gestation and adverse perinatal outcomes.